The Capacity of Multi-Hop Wireless Networks with TCP Regulated Traffic - BANSAL, Sorav (Institutional Knowledge at Singapore Management University, 2002)
We study the dependence of the capacity of multi-hop wireless networks on the transmission range of nodes in the network with TCP regulated traffic. Specifically, we examine the sensitivity of the capacity to the speed of the nodes and the number of TCP connections in an ad hoc network. By incorporating the notion of a minimal acceptable QoS metric (loss) for an individual session, we argue that the QoS-aware capacity is a more accurate model of the TCP-centric capacity of an ad-hoc network. We study the dependence of capacity on the source application (Telnet or FTP) and on the choice of the ad-hoc routing protocol (ad-hoc on-demand distance vector - AODV, dynamic source routing - DSR or destination-sequenced distance vector - DSDV). We conclude that persistent and non-persistent traffic behave quite differently in an ad-hoc network.